2012
DOI: 10.2174/1874256401206010016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potassium Lactate and Sodium Diacetate Combination to Inhibit Listeria Monocytogenes In Low and High Fat Chicken and Turkey Hotdog Model Systems

Abstract: Effect of potassium lactate (PL) and sodium diacetate (SD) combinations at varying levels were evaluated in low (5%) and high (20%) fat chicken and turkey hotdog model systems. All the samples were surface inoculated with Listeria monocytogenes (approximately 4.6 log cfu/g), vacuum packed and stored at 4 o C for 28 days to determine the effective combination of PL and SD and the effect of fat content on the growth inhibition of L. monocytogenes. In chicken hotdog samples, maximum growth inhibitions (3.4 log cf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Therefore, the development of HACCP plans required plants to locate possible points of contamination or locations that could have compromised the safety of a food product. Since then, more interventions and combinations have been examined that may offer further synergistic potential in chicken meat products (Milillo and Ricke, 2010;Milillo et al, 2011;Ravichandran et al, 2011;Perumalla et al, 2012). Clouser et al (1995) identified evisceration equipment, chill water, and personnel as potential microbial crosscontamination sources during first processing, and Whyte et al (2004) also found significant contamination occurring during typical processing procedures.…”
Section: Food Safety Regulations For Poultry Processing: Past and Curmentioning
confidence: 99%
“…Therefore, the development of HACCP plans required plants to locate possible points of contamination or locations that could have compromised the safety of a food product. Since then, more interventions and combinations have been examined that may offer further synergistic potential in chicken meat products (Milillo and Ricke, 2010;Milillo et al, 2011;Ravichandran et al, 2011;Perumalla et al, 2012). Clouser et al (1995) identified evisceration equipment, chill water, and personnel as potential microbial crosscontamination sources during first processing, and Whyte et al (2004) also found significant contamination occurring during typical processing procedures.…”
Section: Food Safety Regulations For Poultry Processing: Past and Curmentioning
confidence: 99%
“…Sodium diacetate is a natural food preservative with the trade name Alvita that is permitted as a food additive by Food and Drug Administration and WHO and no poisonous effect is reported with its permitted values. Sodium diacetate is usually added to food products and uses as a growth inhibitor for molds (14). Escherichia coli are considered a poisonous factor in most foods.…”
Section: Introductionmentioning
confidence: 99%
“…It is approved and widely used in more than 50 countries (Abdollahzadeh et al 2014). Potassium lactate (PL) and sodium acetate (SA) are also widely used as food preservatives as they are recognized as safe (GRAS) (Perumalla et al 2012). Nitrate (NO 3 − ) has been used since 19th century as a food preservative, especially for meat and meat products.…”
Section: Introductionmentioning
confidence: 99%